The Ethnoecology of Sasak Sade Community: Preserving Nature Identity Culture in Lombok - Muslihatun, Fitri; Nabila, Elya Suci; Herawadini, Fitria; Hidayati, Baiq Ria; Kusuma, Anindita SHM (Jurnal Ilmiah Profesi Pendidikan, 2025)
Sade Village is a traditional Sasak settlement that functions both as a cultural tourism destination and as a center of enduring ethnological and ecological practices. This study aims to explore the ethnological and ecological perspectives of the Sade community and to provide strategic recommendations for preserving the nature identity culture of the Sasak Sade people in support of SDG 11 (Sustainable Cities and Communities) and SDG 12 (Responsible Consumption and Production) in Lombok. The research uses a qualitative ethnographic design through observation, in-depth interviews, and documentation. Informants were selected purposively, particularly adat leaders and community members knowledgeable about ecological regulations. The findings show that the community maintains ancestral rules such as prohibitions on cutting trees without permission, mandatory replanting, and the use of local materials in traditional architecture. However, tourism has introduced challenges, including increased plastic waste and declining youth interest in traditional customs. This study recommends strengthening adat institutions, providing ecological cultural education for youth, and integrating traditional values with modern sustainability strategies to safeguard Sade’s nature identity culture.